Childbearing is not associated with young women’s long-term obesity risk - Robinson, Whitney R. (2013)
Contemporary childbearing is associated with greater gestational weight gain and post-partum weight retention than in previous decades, potentially leading to a more pronounced effect of childbearing on women’s long-term obesity risk. Previous work on the association of childbearing with women’s long-term obesity risk mostly examined births in the 1970s and 1980s and produced mixed results. OBJECTIVE: We estimated the association of childbearing and obesity incidence in a diverse, contemporary sample of 2,731 U.S. women. DESIGN AND METHODS: Propensity-score (PS) matching was used for confounding control when estimating the effect of incident parity (1996 to 2001) on 7-year incident obesity (BMI≥30 kg/m(2)) (2001 to 2008). RESULTS: In the sample, 19.3% of parous women became obese while 16.1% of unmatched nulliparous women did. After PS matching without and with replacement, the differences in obesity incidence were, respectively, 0.0 percentage points (ppts) (95% CI: −4.7 to 4.7) and 0.9 ppts (95% CI: −4.9 to 6.7). Results were similar in analyses of prevalent parity and obesity in 2008 (n=6601) conducted to explore possible selection bias. CONCLUSIONS: These results imply that, in contemporary U.S. parous women in their late 20s and early 30s, childbearing may not increase obesity incidence.